(untitled) (Ricos Biology, 2025)
The unending rise of antimicrobial resistance (AMR) is a serious threat to modern medicine. It makes infections that used to be treatable deadly and weakens the basis of surgical and cancer care. The discovery of novel antimicrobial classes with mechanistically distinct action is therefore a critical global health priority. Antimicrobial peptides (AMPs) represent a promising frontier in this endeavor, offering rapid, often non-specific mechanisms that challenge bacterial adaptation. The entomopathogenic bacteria of the genus Xenorhabdus have evolved into biochemical powerhouses, producing a staggering array of AMPs to survive within insect hosts while living in an obligate mutualism with Steinernema nematodes. This review provides a comprehensive analysis of the diverse classes of AMPs derived from Xenorhabdus, categorizing them into non-ribosomal peptides (NRPs) like the xenocoumacins and PAX peptides and ribosomally synthesized and post-translationally modified peptides (RiPPs) such as lasso peptides and novel bacteriocins. We delve deeply into their genetic basis, biosynthetic pathways, and multifaceted mechanisms of action, which range from membrane disruption and iron sequestration to intracellular targeting of essential processes. We further synthesize the evidence for their efficacy against multidrug-resistant ESKAPE pathogens, fungi, and protozoa, while critically evaluating the challenges of toxicity, stability, and scalable production. Finally, we present a forward-looking perspective on how advanced genomics, synthetic biology, and bioengineering strategies are poised to unlock the full potential of the Xenorhabdus pharmacopoeia, transforming these ecological weapons into a new generation of anti-infective agents.